Bernard Shaw and the BBC - Conolly, L. W. (Leonard W.) (Book collections on Project MUSE., 2009)
Drawing on extensive archival materials held in England, the United States, and Canada, Bernard Shaw and the BBC presents a vivid portrait of many contentious issues negotiated between Shaw and the public broadcaster.